The legal implications of electronic letter of credit as a cross border trade payment mechanism : Botswana as a case study - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
Over the years, the electronic letters of credit evolved as one of the developments to meet the international trade demands coupled with the exponential technology advancements of the current times which whetted an appetite for superfluous trade and competitiveness in the trade industry. Just like legal discrepancies pursuant to the use of the letter of credit in international trade, this too demanded some legal architecture to govern its utilization. However, unlike the traditional letters of credit, there are more legal stumbling blocks concerning this form of letters of credit. The primary legal constraints being, lack of legal recognition by the courts because of their nature (being data messages); lack of recognition in the laws of contracts (digital signatures, digital contracts), public perception more especially most of the developing countries, who because of lack of technology, resources and skilled man power, lacked knowledge on the advantages of technology advancement. So, the study interrogates the legal implications of an electronic letter of credit in the international trade transactions using Botswana as a case study. Importantly, it investigates the completeness and sufficiency of the legal regimes in Botswana to enable operation of the electronic letter of credit. The conclusions are that the Botswana e-legislation drafts so far are complete as regard to the legal principles enabling electronic transactions. It also argues that the laws are comprehensive enough, receptive to the electronic documents including the upcoming developments in technology and more importantly, the fact that it provides a level playing field for all the players by protecting the rights of the users of electronic transactions in general.